Numerical simulation for VIV of a long flexible cylinder in the time domain. (30th April 2018) - Huang, Zhiyong; Deng, Zhengzhi; Liu, Dahui; Bai, Yong
ABSTRACT: A two-dimensional multi-strip modelling is developed for the simulation of vortex induced vibration of a long flexible cylinder in the time domain. The turbulent model is used for flow motion, and the structural dynamic is solved with the finite element method. The flexible cylinder is simplified as two-dimensional planes based on strip theory, and the cylinder section is constrained to vibrate in the transverse direction. Stepped flow and shear flow boundary conditions are tested with this multi-strip numerical modelling, and results of response amplitudes, fluid forces and added mass along the spanwise of the flexible cylinder are extensively investigated. Both standing wave and travelling wave responses are obtained under the stepped flow conditions. The multi-strip modelling has a good prediction in low module response, while acceptable results for high module response. In addition, the 2S and 2P vortex shedding modes are observed along the spanwise of the cylinder.